1989
DOI: 10.1210/endo-125-3-1290
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Impair Bone Resorptive Activity and Viability of Osteoclasts Disaggregated from Neonatal Rat Long Bones*

Abstract: It is generally believed that glucocorticoids cause osteoporosis through a combination of decreased bone formation and increased bone resorption. However, the direct effect of glucocorticoids on osteoclasts has not been determined. We therefore tested the effects of hydrocortisone and dexamethasone on bone resorption by osteoclasts disaggregated from neonatal rat long bones. Hydrocortisone and dexamethasone caused a dose-dependent inhibition of osteoclastic bone resorption in the range 10(-7) to 10(-5) M, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 29 publications
4
42
0
Order By: Relevance
“…Metabolic activity was unaffected when OCs were seeded on bone in the presence of 1.6 mM prednisolone but was negatively affected when seeded on plastic, indicating cell death (data not shown), which has been described previously. (12,14) Taken together, these observations strongly suggest that GCs directly affect OC resorptive behavior. Although the total number of resorptive events and TRACP activity after 72 hours was negatively affected by GCs, they were deeper and appeared more frequently as trenches, and OC collagenolytic activity was found to be elevated more.…”
Section: Gcs Act Directly On Ocs and Alter The Morphology Of Resorptimentioning
confidence: 69%
See 3 more Smart Citations
“…Metabolic activity was unaffected when OCs were seeded on bone in the presence of 1.6 mM prednisolone but was negatively affected when seeded on plastic, indicating cell death (data not shown), which has been described previously. (12,14) Taken together, these observations strongly suggest that GCs directly affect OC resorptive behavior. Although the total number of resorptive events and TRACP activity after 72 hours was negatively affected by GCs, they were deeper and appeared more frequently as trenches, and OC collagenolytic activity was found to be elevated more.…”
Section: Gcs Act Directly On Ocs and Alter The Morphology Of Resorptimentioning
confidence: 69%
“…Our study is in accordance with this absence of effect on resorption area generated by human OCs, (13,15) but not with others, where less purified mouse or rat OCs were used and where GCs rather decreased total resorption areas. (10,12,14) We speculate that this decrease could be due to use of OCs from other animal species or to the presence of other cell types.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…DeFranco et a1 suggested that corticosteroid can increase the activity of existing osteoclasts while inhibiting the production of new osteoclasts (32). Others have found that both hydrocortisone and dexamethasone decreased the activity of isolated osteoclasts (33,34). Corticosteroid has also been shown to induce apoptosis, or programmed cell death, in many cells (35).…”
Section: Discussionmentioning
confidence: 99%